“Healing my Body, Healing the Land”: Healing as Sociopolitical Activism in Reclaiming Witchcraft - Roberts, Rosemary (Ethnologies, 2011)
Healing holds a central place in the tradition of Reclaiming Witchcraft, a branch of contemporary Paganism that unites magic and political activism. Rituals are opportunities to bring about healing and are commonly structured around a three-fold model: healing the self, healing each other and the community, and healing the earth. Through this model, practitioners engage with self-empowerment, community-building and political activism, but conflicts arise over the projection of personal healing techniques onto the larger scale of earth healing. Drawing on empirical research and personal involvement, this paper explores the interconnected web of healing, magic, and activism in the Reclaiming tradition.